MILD STEAM EXPLOSION AND CHEMICAL PRE-TREATMENT OF NORWAY SPRUCE - Kerstin Jedvert,; Anna Saltberg,; Mikael E. Lindström,; Hans Theliander (BioResources, 2012)
The aim of this work is to open up the structure of wood while retaining a large amount of hemicelluloses, in particular (galacto)glucomannans. The effects of pre-treatments on wood meal from spruce (Picea abies) with a reducing agent (NaBH4) combined with steam explosion at very mild conditions were investigated. The effects of steam explosion at 160 °C were studied for various residence times (5 to 35 min) on both water-impregnated wood meal and samples pre-treated with NaBH4. The findings showed that pre-treatment with sodium borohydride stabilized the reducing end-groups of glucomannans and that the treatment was effective both during mild steam explosion, for both long and short residence times, as well as during subsequent treatment in alkali. Extraction experiments at different pH and temperatures showed that the main part of the hemicelluloses still remained in the wood residue after treatment. The molecular weight distributions of the extracted material from the liquors indicated that there were broad molecular distributions and that the molecular weight averages were between 3 and 6 kDa.